What Drives Stock Market Underreaction to Liquidity Shocks? Evidence from Korea* - Jang, Jeewon (Asia-Pacific Journal of Financial Studies, 2022)
Stock-level liquidity shocks have a positive cross-sectional relation to not only contemporaneous returns but also one-month-ahead returns in the Korean stock market, which implies that the stock market underreacts to liquidity shocks. However, the return continuation after the arrival of liquidity shocks is short-lived and disappears in two months in Korea, unlike in the United States. The positive relation between liquidity shocks and one-month-ahead returns is most pronounced for illiquid stocks but not present for liquid stocks, independently of the level of investor attention. However, the effect of limited attention on the positive relation differs somewhat across alternative attention proxies and becomes insignificant after controlling for liquidity. This evidence suggests that the short-lived underreaction to liquidity shocks in the Korean stock market is primarily driven not by inattention but by illiquidity.
Keywords: Illiquidity; Limited investor attention; Liquidity shock; Market efficiency; Underreaction